Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1007/s00330-018-5402-6
|View full text |Cite
|
Sign up to set email alerts
|

Increased unenhanced bowel-wall attenuation: a specific sign of bowel necrosis in closed-loop small-bowel obstruction

Abstract: • Increased unenhanced bowel-wall attenuation is the only sign specific for necrosis • Decreased bowel-wall enhancement is not relevant for differentiating reversible ischemia from necrosis • Preoperative knowledge of bowel necrosis is helpful to plan adequate surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 21 publications
6
23
0
Order By: Relevance
“…Rondenet et al reported that increased unenhanced bowel wall attenuation was the only significant predictor of necrosis in strangulated closed-loop SBO [18]. In our study, a reduced enhancement of the intestinal wall and the existence of closed-loop obstruction were found to be independent predictive factors for bowel resection with SSBO.…”
Section: Discussionsupporting
confidence: 65%
“…Rondenet et al reported that increased unenhanced bowel wall attenuation was the only significant predictor of necrosis in strangulated closed-loop SBO [18]. In our study, a reduced enhancement of the intestinal wall and the existence of closed-loop obstruction were found to be independent predictive factors for bowel resection with SSBO.…”
Section: Discussionsupporting
confidence: 65%
“…Rondenet et al reported that increased unenhanced bowel wall attenuation was the only signi cant predictor of necrosis in strangulated closed-loop SBO [22]. In our study, a reduced enhancement of the intestinal wall and the existence of closed-loop obstruction were found to be independent predictive factors for bowel resection with SSBO.…”
Section: Discussionsupporting
confidence: 64%
“…The experience gained over several decades demonstrates the high value of the radiographic contrast study (RCS) of the intestine in the diagnosis of intestinal obstruction. Various methods of artificial enhancing have been developed and indications for their use have been clearly formulated depending on the anatomical and physiological characteristics of the examined site and the presence of particular clinical manifestations [ 1 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…The positive feature of the ultrasound examination is the determination of access for laparoscopic surgeries; simultaneously, the authors note that this method is accessory and cannot substitute computed tomography. The authors consider that the advantage of computed tomography, unlike ultrasound, is its independence from the researcher; it is fast and does not require barium and has high informativeness [ 1 , 5 , 8 ].…”
Section: Discussionmentioning
confidence: 99%